EFFECTIVENESS OF THE SMART INDONESIA CARD PROGRAM ( KIP ) ON STUDENT LEARNING ACHIEVEMENT IN THE DEPARTMENT OF DIGITAL BUSINESS, STATE UNIVERSITY OF MEDAN - Sitompul, Kristina Pujasari; Hutagalung, Febrianti; Hasibuan, Ramadani Shohiro; Tarigan, Fandy Franata; Ivanna, Julia (UIN Mataram, 2024)
This study aims to ascertain what factors contribute to the ineffectiveness of Smart Indonesia at Medan State University and how well the program is implemented based on Ministerial Regulation No. 10 of 2020 for digital business majors in achieving access to education. This study employed a qualitative technique. Through the use of questionnaires, primary and secondary data sources provided the information that was employed. According to Soerjono Soekamto's assessment of effectiveness, the implementation of the Minister of Education and Culture Regulation No. 10 of 2020 regarding the Smart Indonesia Program at Medan State University, which offers a major in digital business, has not yet reached the anticipated level of effectiveness. This is supported by the study's findings. Aspects of law enforcement, legal considerations, facility and infrastructural conditions, as well as societal and cultural dynamics, are some of the variables that affect it. The challenges faced include problems related to target accuracy, the process of disbursing funds, and the lack of data related to students who are entitled to KIP.